Our approach to cases with fungus balls of the paranasal sinuses - Nabi Erkan, Alper; Köycü, Alper (ENT Updates, 2014)
Objective: To retrospectively evaluate clinical and radiological characteristics of the patients with paranasal sinus fungus ball. Methods: The medical files of nine patients who had been operated between April 2010 and November 2013 in Adana Hospital of the Baflkent University with the diagnosis of fungus balls of paranasal sinuses were analyzed. Patients with fungus infection which was showed tissue invasion, allergic mucin, rich of eosinophil and granulomatous tissue in histopathologic examination were excluded in the study. Demographic characteristics, physical examination findings, results of computed tomography, culture and histopathologic examinations were analyzed. Results: Study population consisted of three men and six women with a mean age of 64.5 (range: 35 to 78) years. In all patients, an intrasinusal hyperdense heterogenous image was detected on paranasal sinus tomograms. Fungus balls were noted in the right maxillary sinus in five (77.7%) and in sphenoid sinus in two (22.3%) patients. Only three (33.3%) patients had not any other systemic disease. All patients underwent functional endoscopic sinus surgery. On histopathological examination, results of all patients were reported as fungus balls. Conclusion: In cases presenting with a systemic disease associated with non-specific symptoms of sinusitis, the presence of a fungus ball should be considered.